Effect of parasitic absorption of the plasmonic cubic nanoparticles on the performance of a plasmonic assisted halide thin-film perovskite solar cell. (15th July 2021) - Heidarzadeh, Hamid
Highlights: The absorption improvement of perovskite solar cell using plasmonic nano-cubes. The effects of parasitic absorption inside the nanoparticles are evaluated. The enhanced electrical field due to LSPR is responsible photcurrent improvement. The photocurrent improvement from 17.70 mA/cm 2 to 23 mA/cm 2 using nano-cubes. Some guidelines for a realistic understanding of plasmonic-based solar cells. Abstract: In the current investigation, the plasmonic nano-cubes were used to improve the absorption of an organic-inorganic hybrid crystalline-based CH3 NH3 PbX3 perovskite solar cell. One of the critical challenges of plasmonic nanoparticles is their parasitic absorption that would compensate or even surpass the effect of plasmonic nanoparticles. So, the effects of parasitic absorption inside the nanoparticles were evaluated. By incorporating the plasmonic effect of nano-cubes, the parasitic absorption of Al and Ag nano-cubes and the absorption spectrum of the perovskite absorber were calculated. The parasitic absorption of nano-cubes was subtracted, and net absorption was obtained before calculating the photocurrents. Optimization is done to find the best nano-cubes edges and the period of the unit cell. Using Al and Ag nano-cubes increases the photocurrent increase to 23 mA/cm 2, and 22 mA/cm 2 in a cell with a thickness of 200 nm, respectively. The photocurrent of the reference cell is 17.70 mA/cm 2 . So, the enhancement factors of 29%, and 24.3% were obtained for them in comparison to the reference cell, respectively. Moreover, the boosted photon absorption was confirmed through the electrical field distribution and the profiles of generation rate. The results can be used to establish some guidelines for a realistic understanding of plasmonic resonance-based photovoltaic devices.